A comparison of African buffalo, N'Dama and Boran cattle as reservoirs of Trypanosoma vivax for different Glossina species - Moloo, S.K.; Gettinby, George; Olubayo, R.O.; Kabata, J.M.; Okumu, I.O. (Cambridge University Press, 1993)
Teneral Glossina morsitans centralis were fed on the flanks of African buffalo, N'Dama or Boran cattle infected with Trypanosoma vivax IL 2337. The infected tsetse were maintained on goats and on day 25 after the infected feed, the surviving tsetse were dissected to determine the infection rates. The mean mature infection rates (% ± S.E.) in the tsetse fed on buffalo, N'Dama and Boran cattle were 34-3 ± 9-9, 33-7 ± 13-4 and 58-9 ± 7-1, respectively. Logistic regression analysis indicated that infection rates in the labrum and hypopharynx of the tsetse were significantly lower when fed on the infected buffalo or N'Dama than Boran cattle. Similarly, the risk of infection was significantly lower in male than female tsetse. When teneral G. m. centralis, G. pallidipes, G. p. gambiensis, G. brevipalpis and G. longipennis were fed simultaneously on either the buffalo cow, the N'Dama bull or the Boran steer infected with T. vivax IL 2337, the mature infection rates were higher in the two morsitans group than the two fusca group tsetse, whilst G. p. gambiensis was relatively refractory to the infection, irrespective of the host species on which they fed. Logistic regression analysis indicated that the infection rates in the labrum and hypopharynx were significantly different amongst the five tsetse species for each of the three infected host animals. Nevertheless, the trypanotolerant African buffalo and N'Dama cattle may serve as reservoirs of T. vivax infection as can trypanosusceptible Boran cattle.